Role of Innate Immunity in Pediatric Post-transplant Idiopathic Liver Fibrosis - Wu, Yue; Huang, Mingzhu; Sun, Haojie; Zhou, Xiying; Zhou, Ruoqiao; Gu, Guangxiang; Xia, Qiang (Frontiers in Immunology, 2020)
Pediatric post-transplant idiopathic liver fibrosis is so far an unexplained graft fibrosis that occurs in symptom-free children recipients without acute rejection and surgical complications. Despite the lack of consensus, the development of pediatric post-transplant idiopathic liver fibrosis is believed to be a result of multiple potential factors, including ischemia-reperfusion injury, allogeneic acute and chronic rejection, viral hepatitis recurrence, opportunistic infection, and drug-induced liver damage. Among them, there is growing evidence that innate immunity may also have a unique role in this progression. With knowledge at hand, we will review the features of pediatric post-transplant idiopathic liver fibrosis, and discuss the current studies illustrating the potential mechanisms of liver allograft tolerance induced by intrahepatic innate immunity, the role of components including Toll-like receptors (TLRs), interferons (IFN), dendritic cells (DC), natural killer cells (NK cells), NKT cells, neutrophils and Kupffer cells, as well as their possibly relevant role in the development of pediatric post-transplant idiopathic liver fibrosis.